A national survey of Russian physicians' knowledge of diagnosis and management of food-induced anaphylaxis. Issue 7 (20th July 2017) - Munblit, Daniel; Treneva, Marina; Korsunskiy, Ilya; Asmanov, Alan; Pampura, Alexander; Warner, John O
Abstract : Objectives: Food allergy is an increasing burden worldwide and is a common problem within paediatric populations, affecting 5%–8% of children. Anaphylaxis caused by food proteins is a potentially life-threatening condition and all healthcare practitioners should be aware of its recognition and management. Russia is the largest country in Europe but it is still unknown whether physicians are prepared to diagnose and manage food-induced anaphylaxis effectively. We aimed to examine physicians' knowledge of diagnosis and management of food-induced anaphylaxis. Setting, population and outcomes: A survey was designed and published online at VrachiRF.ru website (for registered Russian-speaking practicing physicians). We obtained information on respondents' clinical settings, experience and specialty. Survey questions were based on a characteristic clinical scenario of anaphylaxis due to food ingestion. Outcome measures consisted of correct answers to the anaphylaxis diagnosis and management questions. Results: From a total of 707 of physicians accessed in the survey, 315 (45%) responded to the clinical scenario. 16 respondents reported training in allergy-immunology and have been excluded from the analysis, leaving the final sample size of 299. Respondents were paediatricians (68%) and other specialties adult physicians (32%). Overall, 100 (33%) of respondents diagnosed anaphylaxis, but only 29% of those making the correct diagnosis administered adrenalin (1:1000) intramuscular. Respondents working in secondary/tertiary clinics diagnosed anaphylaxis significantly more often (p=0.04) when compared with primary care/private practice physicians. This difference was also apparent as the most important influence on responses in the multivariate analysis. Conclusions: In this national sample of Russian physicians, we found poor knowledge in both anaphylaxis diagnosis and management. Our data show that the chance of being properly diagnosed with anaphylaxis is 33% and being appropriately treated with adrenalin is 10%. These findings highlight lack of anaphylaxis knowledge among Russian physicians, both paediatricians and other specialists and illustrates the urgent need for allergy/anaphylaxis training.